Next-generation sequencing in precision oncology: challenges and opportunities. (July 2014) - Kruglyak, Kristina M; Lin, Erick; Ong, Frank S
<x xml:space="preserve">Abstract</x> High throughput gene sequencing is transforming the utilization of genomics in patient care by providing physicians with a powerful tool to aid the diagnosis and management of disease, particularly in precision oncology. As next-generation sequencing (NGS)-based diagnostic assays are developed, significant hurdles such as assessing tumor heterogeneity, characterizing 'driver' and 'passenger' mutations, typing molecular signatures of individual cancers and determining limits of detection pose significant challenges for clinical laboratories and downstream bioinformatics analyses. Despite these challenges, NGS has the potential to affect all facets of cancer treatment, including early detection and diagnosis through cancer screening in at-risk populations and assessing therapeutic efficacy by detection of circulating tumor DNA via noninvasive blood draws. As the utilization of NGS in precision oncology matures, NGS-based laboratory tests could be used throughout the evolution of cancer in patients and allow for cancers to be monitored and managed as a chronic disease, rather than an acute condition.